Pengaruh Kualitas Pelayanan dan Emosional Terhadap Kepuasan Konsumen Rujak Asinan Nyonya Kim - Angelina, Theresia; Elizabeth, Sri Megawati (MDP Student Conference, 2024)
The purpose of this study was to analyze the influence of service quality and emotional impact on consumer satisfaction with Rujak and Asinan Nyonya Kim partially and simultaneously. This study uses a questionnaire distribution method with a likert scale, with a total of 477 respondents. The sampling technique in this study uses the Slovin method and with the help of SPSS software. This study used quantitative descriptive method, the subjects in this study is the people of Palembang city who have purchases at Rujak and Asinan Nyonya Kim. The results of this study showed that partially and simultaneously the service quality and emotional variables have a positive and significant influence on consumer satisfaction.